ANALISIS KARAKTERISTIK PANJAR MAJU DAN PANJAR MUNDUR PADA DIODA 1N4007 - Mukti Ali; Fitrani Kadir; Muh. Syihab Ikbal (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2023)
The purpose of this study is to describe the characteristics of changes in current and voltage in rectifier diodes with the 1N4007 series in the forward bias and reverse bias states and to be able to describe and explain the characteristics of the current-voltage (I-V) and 1N4007 rectifier diodes. The method used in this study is the experimental method. The equipment and components used in the research are 1N4007 diode, B10K potentiometer, 100Ω resistor, ammeter and voltmeter. The variables measured in this study are the control variable (voltage source), the measurement variable (diode voltage), the response variable (diode current strength). The relationship that is formed from the current strength and voltage on the diode is in the form of a linear curve at the voltage value below the diode working voltage, and will increase significantly when the diode voltage is at working voltage. Based on the analysis of the graph and the load line, it can be concluded that the 1N4007 diode is a diode derived from silicon material with a working voltage value of 0.6 -0.7volts and will only pass current in one direction and will not pass current in a bias state. backwards as long as the diode has not reached its breakdown voltage.